Penyuluhan Penyakit Mulut dan Kuku (LSD) Untuk Kelompok Peternak Dalam Rangka Peningkatan Kesejahteraan Masyarakat - Suripto; Lumino Basia; Uswatun Khasanah (Politeknik Negeri Cilacap, 2024)
Community service discusses Livestock Vesicular Diseases (LSD) foot and mouth disease in cattle farmer groups who are susceptible to this disease. Community service activities are carried out at the Lestari Migunani Livestock Group, Nangsri Lor, Candirejo, Semanu, Gunungkidul with the main focus on overcoming foot and mouth disease in livestock. By referring to the extension material through livestock community meetings and educational materials provided face-to-face, it is hoped that there will be an increase in active community involvement, and collaboration with village government agencies to prevent foot and mouth disease outbreaks in Nangsri Lor, Candirejo, Semanu, Gunungkidul. Community service activities aim to provide understanding to livestock group members about foot and mouth disease and prevention strategies, to create a productive livestock community that supports the family economy. This community service activity also provides concrete solutions to livestock health problems but also empowers communities to manage animal health independently, improve welfare, and build economic resilience through community livestock farming. The results of this community service activity were that there were 23 participants (88.5% of the total) who stated that they were delighted with the community service program that was held, this shows that the level of participant satisfaction with the program provided was high.